The Destruction of Cultural Property as a Weapon of War ISIS in Syria and Iraq - Turku, Helga (Springer International Publishing, 2018)
This book aims to advance the understanding of cultural property in armed conflict, and its significance for anti-terrorism and peace-building strategies. As the author argues, ISIS' orchestrated theft and destruction of cultural property has become a tactic of war. Through a historical, political, and legal analysis, this book explains the pathology of radical groups' behavior toward cultural objects as part of their terror campaign. Using constructivist ideas, it explains the importance of cultural property in the context of short-term and long-term security and analyzes the evolution of laws and policies to protect it.